Nonlinear optical characterization of the gold nanoparticles coated by the thiols - Lesiak, Piotr; Wójcik, Michał (Photonics Letters of Poland, 2011)
Structured nanomaterials have great potential applications based on their unusual optical properties, such as a negative refractive index [1], plasmon waveguiding [2] or nonlinear optics. In this paper we present the nonlinear optical characterization of gold nanoparticles coated by thiols with the ratio of mesogenic to n-alkyl thiols varying from 1:2 to 1:1 in a toluene suspension using the Z-scan technique. The type of mesogenic molecule in the metal coating had a profound influence on the gold-cluster self-assembly. To check how these clusters affect the nonlinear properties we use two different polarizations of a laser beam - linear and circular. Full Text: PDF References: J.B. Pendry, "Negative Refraction Makes a Perfect Lens", Phys. Rev. Lett. 85, 3966 (2000).[CrossRef] S.A. Maier, M.L. Brongersma, P.G. Kik, S. Meltzer, A.A.G. Requicha, H.A. Atwater, "Plasmonics?A Route to Nanoscale Optical Devices", Adv. Mater. 13, 1501 (2001). [CrossRef] M. Sheik-Bahae, A.A. Said, E.W. Van Stryland, "High-sensitivity, single-beam n2 measurements", Opt. Lett. 14, 955 (1989). [CrossRef] M. Sheik-Bahae, A.A. Said, T.H. Wei, D.J. Hagan, E.W. Van Stryland, "Sensitive measurement of optical nonlinearities using a single beam", J. Quant. Electr. 26, 760 (1990). [CrossRef] B.E.A. Saleh, M.C. Teich, Fundamentals of Photonics (John Wiley & Sons, Inc., second edition, 2007).